Inovasi Pelayanan Publik Berbasis E-Government di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bangka - Ragil Fitri Rahayu; Ibrahim Ibrahim (Inovbook, 2023)
This study attempts to analyze the implementation of public services innovation in Population and Civil Registry Office in Bangka District. Regarding to Executive Order Number 3 of 2003 on National Development Strategy of E-Governmentin Bangka District manage to improve the public services. However, there are complex problem of the implementation especially in population proposition. In the case moreover, citizen and civil service staff demand to be adapted. The occurring problem usually appeared is the unclear document of citizen. This study use theory of Innovation devotion by Everett M. Rogers, and use qualitative descriptive method. In the other hand, research data collecting use interview, observation, and documentation. The result of this study is to prove E-Governmentpolicy not completely gave the convenience to citizen, and also Population and Civil Registry Office in Bangka District is not ready to apply it. There are three digital innovations utilize by Population and Civil Registry Office in Bangka District, BANGMUDA (Bangka Mudah Dapat Akta), Gerbang Terindak and Matras Bangka. The implementation of E-Governmentpublic services innovation in Population and Civil Registry Office in Bangka District is not optimal. In fact, there are some points which influence the implementation of E-Governmentin Population and Civil Registry Office in Bangka District, regardless to the advantage or disadvantage, which are: first, creating the good government, second, reduce the corruption problem, third, the efficiency of time and space, fourth, there are numbers of citizen lack of technology and information, fifth, citizen ignorance, sixth, people culture, and seventh, internet problem.